The role and choice criteria of antihistamines in allergy management – expert opinion - Kuna, Piotr; Jurkiewicz, Dariusz; Czarnecka-Operacz, Magdalena M.; Pawliczak, Rafał; Woroń, Jarosław; Moniuszko, Marcin; Emeryk, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Allergic diseases are the most common chronic conditions lasting throughout the patient’s life. They not only cause significant deterioration in the quality of life of patients but also lead to significant absenteeism and reduced productivity, resulting in very high costs for society. Effective and safe treatment of allergic diseases is therefore one of the main challenges for public health and should be carried out by all the specialists in family medicine, internists and paediatricians in collaboration with allergists, otorhinolaryngologists and dermatologists. Antihistamines are most commonly used in the treatment of allergies. Several dozen drugs are available on the pharmaceutical market, and their generic forms are advertised widely as very effective drugs for the treatment of allergic diseases. What is the truth? What are the data from clinical trials and observational studies? Are all drugs equally effective and safe for the patient? According to a panel of experts representing various fields of medicine, inappropriate treatment of allergies can be very risky for patients, and seemingly equally acting medications may differ greatly. Therefore, a panel of experts gathered the latest data from the entire scientific literature and analysed the latest standards and recommendations prepared by scientific societies. This paper provides a summary of these studies and highlights the importance for the patient of the proper choice of drug to treat his allergies.